EDUCATIONAL AND AESTHETIC VIEWS OF OTKIR HASHIMOV - Soberova, Mohira (FILOLOGIYA UFQLARI JURNALI, 2024)
Abstract the article states that O'tkir Hoshimov is one of the unique creators of Uzbek literature with his unique prose works, educational works, journalistic works, literary-critical articles, and the writer's educational, spiritual they will talk about their opinions on education issues.